(untitled) (AYUSHDHARA, 2016)
Cerebral palsy is a non-progressive disorder of posture and movement often associated with epilepsy and abnormalities of speech, vision and intellect, which is the leading cause of disability in children leads to dependency on family and society. It results from a defect or lesion of the developing brain. There are 25 lakhs of CP children in India. Its incidence is 3.6 per 1000 live births. According to Ayurveda CP can be clinically correlated with Vata Vyadhi such as Ekanga Roga, Pangutwa, Pakshaghata, Sarwanga Roga or combination of other Vata Prakopaka Lakshana. It is caused due to Shiromarmabhighata. At present there is no cure for this disease. But Ayurvedic interventions such as Abhyanga, Pindasweda, Basti Chikitsa, Nasya with internal Vata Shamaka, Brumhana and Medhya Kalpa shows better results in CP to improve physical activity, movements and quality of life. As The main causative factor is Vata and all the acharyas including Kashyapa have mentioned Vasti karma as the best line of treatment in alleviating vitiated Vata.. In present study, the management of CP is done by the Sishu namaka vasti for 11 days to increase functional ability by decreasing spasticity. Some positive result have been noticed after treatment.